# include & lt; Stdio. H>
# include & lt; Stdlib. H>
# define M 4
A void fun (int *)
{
Int I, j, k, m, p;
For (I=M; I> 0; I -)
{
K=* (a + M - 1);
For (j=M - 1; J & gt;=0; J -) {
* (a + j + 1)=* (a + j);
}
* a=k;
For (m=0; mPrintf (" % d ", * (a + m));
printf("\n");
}
}
Int main () {
Int a [M]={1, 2, 3, 4};
Fun (a);
}
CodePudding user response:
* (a + j + 1)=* (a + j)Like crossing the line, a * (a + 4)
* (a + m) is equivalent to a [m]
Mean to print a [0], a [1], a [2], a [3]
* (a +... ) you can use a [...] Replace
This should be well understood
CodePudding user response:
K=* (a + M - 1);//the last element of an array is assigned to the variable kFor (j=M - 1; J & gt;=0; J -) {
* (a + j + 1)=* (a + j);//loop moving back the elements of an array is a
}
* a=k;//array value of the first element is the original array now the last one